2013
DOI: 10.1098/rstb.2012.0490
|View full text |Cite
|
Sign up to set email alerts
|

The response of Arctic vegetation and soils following an unusually severe tundra fire

Abstract: Fire causes dramatic short-term changes in vegetation and ecosystem function, and may promote rapid vegetation change by creating recruitment opportunities. Climate warming likely will increase the frequency of wildfire in the Arctic, where it is not common now. In 2007, the unusually severe Anaktuvuk River fire burned 1039 km2 of tundra on Alaska's North Slope. Four years later, we harvested plant biomass and soils across a gradient of burn severity, to assess recovery. In burned areas, above-ground net prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
157
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(180 citation statements)
references
References 57 publications
(130 reference statements)
16
157
2
Order By: Relevance
“…This is the largest fire on record (1039 km 2 burned) for the tundra biome and it doubled the cumulative area burned north of 68°N in that region since 1950 [6]. This fire has been well-studied [6][7][8][9], but appears to be a novel expression in the tundra fire record as a fire that started mid-summer (July) and persisted late into the growing season (October) and exhibited greater burn severity than typical tundra fire events [8]. Alternatively, it has been suggested that with climate change the Anaktuvuk River Fire may represent the new normal [6].…”
Section: Introductionmentioning
confidence: 93%
“…This is the largest fire on record (1039 km 2 burned) for the tundra biome and it doubled the cumulative area burned north of 68°N in that region since 1950 [6]. This fire has been well-studied [6][7][8][9], but appears to be a novel expression in the tundra fire record as a fire that started mid-summer (July) and persisted late into the growing season (October) and exhibited greater burn severity than typical tundra fire events [8]. Alternatively, it has been suggested that with climate change the Anaktuvuk River Fire may represent the new normal [6].…”
Section: Introductionmentioning
confidence: 93%
“…Phoenix and Bjerke (2016) propose that tundra browning could be more "event driven" than greening, caused by fire (Bret-Harte et al 2013), extreme winter warming (Bokhorst et al 2011), other anomalous weather events (e.g., frost damage), and outbreaks of insect and fungal pests (Graglia et al 2001;Bjerke et al 2014). Another potential cause of tundra browning could be increases in herbivore populations (Pederson et al 2013;Hupp et al 2015;Barrio et al 2016).…”
Section: August 2017 State Of the Climate In 2016mentioning
confidence: 99%
“…canopy N s 21 , with a lower quantum yield than in the analyses based on LAI. The R 0 parameter varied from 0.6 to 1.0 mmol CO 2 g 21 canopy N s 21 . Although the units of P maxL and R 0 in these regressions were different when N T rather than LAI was used, the ratios of these two parameters stayed about the same; P maxL was always approximately 10 -12 times the value of R 0 no matter what the units were (table 4 versus table 5).…”
mentioning
confidence: 99%